Evaluación de la Sostenibilidad Ambiental de Agro Ecosistemas en el Páramo Fuctin de la Comunidad Chanchaló aplicando la Metodología Safa, Cantón Salcedo, Provincia Cotopaxi, 2018. - Saca Plasencia, Mayra Nataly (2019)
This research was carried out to evaluate the environmental sustainability of Fuctín ecosystems highlands, in Chanchaló community applying the SAFA methodology: It is about good governance against the community that offers incentives for the adoption of sustainable practices, to impose standards and costs for actions that deplete or degrade natural resources. Environmental Integrity, the caring and conservation of highlands is fundamental aspect that includes the economic growth of the community since they offer important resources in the development of the inhabitants and their lives, in addition it is a neglected aspect to the point that presents these ecosystems those are at risk because the mismanagement given around them and benefit. Economic Resilience, is the investment of added value that private sector investment makes in the strengthening of community capacities, in addition it involves challenges in economic activity that implies the use of labor, land and capital to produce goods and services to meet the needs of the community inhabitants.